Empowering Pesantren as an Anti-Global Climate Change Center in Jember - Nurul Anam; Elok Rufaiqoh; Sofiah Sofiah (GUYUB: Journal of Community Engagement, 2024)
Global climate change has been considered a more threatening problem to face. In particular, establishing a pesantren-based anti-global climate change center within Al-Qodiri Islamic Boarding School is seen as the mitigation system. As this program is meant to be a community service program, the ABCD community empowerment method was used. The results suggested that: First, in the research planning (define, discovery, dream, and design), the most critical assets to be developed were the human resource assets of the santri (lit. student). The objective is to develop the quality of the santri as the human resource asset to realize the pesantren-based anti-global climate change center—the service programs in the form of counseling, training, and mentoring. Second, the holistic transformation-based service was done through applicative and evaluative stages, which has improved the quality of the human resource assets of Al-Qodiri Islamic Boarding School Community holistically both in the aspects of knowledge, creativity, and ascertaining character awareness to establish an anti-global climate change society.